Differential contribution of three immune checkpoint (VISTA, CTLA-4, PD-1) pathways to antitumor responses against squamous cell carcinoma. (June 2016) - Kondo, Yuta; Ohno, Tatsukuni; Nishii, Naoto; Harada, Kiyoshi; Yagita, Hideo; Azuma, Miyuki
Highlights: VISTA blockade increases T cell recruitment in the tumor microenvironment. VISTA blockade converts CD8 + T cells to finally differentiated effector T cells. VISTA blockade enhances multifuntionality of CD8 + T cells. Combined CTLA-4 and VISTA blockade is more efficacious. Inhibition of regulatory T cell recruitment within tumors is critical. Summary: V domain-containing Ig suppressor of T-cell activation (VISTA)/PD-1H is a novel immune checkpoint molecule for regulating T-cell activation. We examined the effects of anti-VISTA mAb monotherapy and combination therapy with CTLA-4 or PD-1 blockade in a squamous cell carcinoma (SCCVII) model. VISTA monotherapy did not show clear tumor growth regression, but efficiently induced CD8 + T cell activation by converting resting and exhausted cells into functional effector cells. VISTA monotherapy did not inhibit recruitment of regulatory T cells (Tregs) in the tumor microenvironment (TME). As an additional treatment to VISTA, CTLA-4 blockade, but not PD-1 blockade, elicited further tumor regression. The CTLA-4 and VISTA combination efficiently inhibited Treg recruitment and increased the ratios of both CD8 T/Treg and CD4 conventional T (Tcon)/Treg in the TME, whereas the PD-1 and VISTA combination dramatically increased tumor-recruiting CD8 + T cells, but markedly reduced the Tcon/Treg ratio. Our results demonstrate that VISTA blockade efficiently converts CD8 + T cells into functional effector T cells, but is not sufficient to regress tumor growth due to weak Treg suppression in the TME. Our results suggest that combined CTLA-4 and VISTA blockade is more efficacious than combined PD-1 and VISTA blockade for tumors like head and neck squamous cell carcinoma in which Treg-mediated immune regulation is dominant.